Patterns of Gene Expression in the Bovine Corpus Luteum Following Repeated Intrauterine Infusions of Low Doses of Prostaglandin F2alpha - Atli, Mehmet O.; Bender, Robb W.; Mehta, Vatsal; Bastos, Michele R. [UNESP]; Luo, Wenxiang; Vezina, Chad M.; Wiltbank, Milo C. (Soc Study Reproduction, 2012)
Natural luteolysis involves multiple pulses of prostaglandin F2alpha (PGF) released by the nonpregnant uterus. This study investigated expression of 18 genes from five distinct pathways, following multiple low-dose pulses of PGF. Cows on Day 9 of the estrous cycle received four intrauterine infusions of 0.25 ml of phosphate-buffered saline (PBS) or PGF (0.5 mg of PGF in 0.25 ml of PBS) at 6-h intervals. A luteal biopsy sample was collected 30 min after each PBS or PGF infusion. There were four treatment groups: Control (n = 5; 4 PBS infusions), 4XPGF (4 PGF infusions; n = 5), 2XPGF-non-regressed (2 PGF infusions; n = 5; PGF-PBS-PGF-PBS; no regression after treatments), and 2XPGF-regressed (PGF-PBS-PGF-PBS; regression after treatments; n = 5). As expected, the first PGF pulse increased mRNA for the immediate early genes JUN, FOS, NR4A1, and EGR1 but unexpectedly also increased mRNA for steroidogenic (STAR) and angiogenic (VEGFA) pathways. The second PGF pulse induced immediate early genes and genes related to immune system activation (IL1B, FAS, FASLG, IL8). However, mRNA for VEGFA and STAR were decreased by the second PGF infusion. After the third and fourth PGF pulses, a distinctly luteolytic pattern of gene expression was evident, with inhibition of steroidogenic and angiogenic pathways, whereas, there was induction of pathways for immune system activation and production of PGF. The pattern of PGF-induced gene expression was similar in corpus luteum not destined for luteolysis (2X-non-regressed) after the first PGF pulse but was very distinct after the second PGF pulse. Thus, although the initial PGF pulse induced mRNA for many pathways, the second and later pulses of PGF appear to have set the distinct pattern of gene expression that result in luteolysis.
Keywords: corpus luteum; gene expression; hormone action; luteolysis; mRNA; prostaglandins